The growing out-of-school time field : past, present, and future - Donahue, Tara; Malone, Helen Janc (Current issues in out-of-school time., 2018)
Current Issues in Out-of-School Time, is designed with a purpose to disseminate original research and promising practices that further the OST field. This first book sets the foundation on which the series rests upon, by offering an analysis of the progress made since the 2000s, as well as by looking toward the future for areas of considerations. Leading OST experts explore latest knowledge, intentionally bridging research and practice, and propose new areas of inquiry within each of the following six sections: 1. OST as a vehicle for young people's development; 2. socio-cultural dimensions of OST; 3. professional development within OST; 4. research- and evaluation-informed field; 5. OST advocacy; 6. future directions for the OST field. The OST field has grown considerably over the last two decades. Today, we have the frameworks, practice- and research-based knowledge and tools, and burgeoning paths to advance the field across multiple dimensions: demographic, stakeholder groups, contexts, systems and sectors, and disciplines. The hallmark of the OST field has been the ability to remain agile and adaptable to change in a way that complements the field and supports all children and young people in diverse ways. This anthology is designed to be a platform for research-practice discussions and future directions that could further grow, sustain, and improve the field. We hope this book inspires both reflections and conversations on the OST field.